Global processing in amblyopia: a review - Hamm, Lisa M.; Black, Joanna; Dai, Shuan; Thompson, Benjamin (Frontiers in Psychology, 2014)
Amblyopia is a neurodevelopmental disorder of the visual system that is associated with disrupted binocular vision during early childhood. There is evidence that the effects of amblyopia extend beyond the primary visual cortex to regions of the dorsal and ventral extra striate visual cortex involved in visual integration. Here we review the current literature on global processing deficits in observers with either strabismic, anisometropic or deprivation amblyopia. A range of global processing tasks have been used to investigate the extent of the cortical deficit in amblyopia including: global motion perception, global form perception, face perception and biological motion. These tasks appear to be differentially affected by amblyopia. In general, observers with unilateral amblyopia appear to show deficits for local spatial processing and global tasks that require the segregation of signal from noise. In bilateral cases, the global processing deficits are exaggerated, and appear to extend to specialized perceptual systems such as those involved in face processing.